Penerapan Sistem Pengendalian Intern dalam Meminimalkan Kredit Macet : Studi Kasus pada PT Sinar Sosro Kp Sawangan - Hastoni, Hastoni; Nugraha, Andi (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
This research was carried out to get estimation of how far the quality of credit selling system and procedure, the internal control system of credit selling, credit management, and how far the internal control of credit selling has influence toward credit quality raising and minimize stuck claim. The outcome of this research indicates that generally the implementation of credit selling system and procedure has gone smoothly. This matter can be observed from the existence of duty and authority at each departement in line with job description, the internal control practice of credit selling focused at the organization, procedure, and recording, as well as from healty practices. It can be detected on gradually and incessantly process from credit submission up to the submission approved. Keywords: Internal Control; Credit.